WREN---an environment for component-based development. - Lüer, Chris (Software engineering notes.)
Prior research in software environments focused on three important problems---tool integration, artifact management, and process guidance. The context for that research, and hence the orientation of the resulting environments, was a traditional model of development in which an application is developed completely from scratch by a single organization. A notable characteristic of component-based development is its emphasis on integrating independently developed components produced by multiple organizations. Thus, while component-based development can benefit from the capabilities of previous generations of environments, its special nature induces requirements for new capabilities not found in previous environments. This paper is concerned with the design of component-based development environments, or CBDEs. We identify seven important requirements for CBDEs and discuss their rationale, and we describe a prototype environment called WREN that we are building to implement these requirements and to further evaluate and study the role of environment technology in component-based development. Important capabilities of the environment include the ability to locate potential components of interest from component distribution sites, to evaluate the identified components for suitability to an application, to incorporate selected components into application design models, and to physically integrate selected components into the application.